Endoscopic characterization of sessile serrated adenomas/polyps with and without dysplasia - Bouwens, Mariëlle W. E.; van Herwaarden, Yasmijn J.; Winkens, Bjorn; Rondagh, Eveline J. A.; de Ridder, Rogier; Riedl, Robert G.; Driessen, Ann; Dekker, Evelien; Masclee, Ad A. M.; Sanduleanu, Silvia (Endoscopy, 2014)
Background and study aims: Sessile serrated adenomas/polyps (SSA/Ps) are precursors of colorectal cancer (CRC), but their endoscopic detection can be difficult. We therefore examined the endoscopic characteristics of SSA/Ps with and without dysplasia in a cross-sectional study.Patients and methods: We reviewed clinical, endoscopic, and histopathologic data from patients undergoing colonoscopy between February 2008 and February 2012. We categorized colorectal polyps according to anatomic site, size, and shape, and classified serrated polyps using the World Health Organization (WHO) classification. Multiple logistic regression analyses examined potential differences regarding site, size, and shape between SSA/Ps and colorectal adenomas (overall and advanced only).Results: We examined 7433 patients (mean age 59 years, 45.9 % men) with 5968 colorectal polyps. In total, we found 170 SSA/Ps (170/5968, 2.9 %), including 63 SSA/Ps with dysplasia (1.1 %) and 107 SSA/Ps without dysplasia (1.8 %). Compared with SSA/Ps with dysplasia, SSA/Ps without dysplasia were more often proximally located (odds ratio [OR] 3.3, 95 % confidence interval [95 %CI] 1.7 – 6.4), but less often < 6 mm in size (OR 0.6, 95 %CI 0.3 – 1.1). No significant differences were found regarding location between SSA/Ps with dysplasia and advanced adenomas (proximal colon, 47.6 % vs. 40.1 %). However, SSA/Ps with dysplasia were more often < 6 mm in size than advanced adenomas (OR 0.3, 95 %CI 0.2 – 0.5). Of the 63 dysplastic SSA/Ps, 6 (9.5 %) contained high grade dysplasia, but none invasive carcinoma.Conclusions: SSA/Ps with dysplasia are frequently < 6 mm in size, located throughout the colon and 9.5 % of them contain high grade dysplasia. These findings underscore the importance of high quality colonoscopic examination to maximize protection against CRC.